Equality of opportunity and the distribution of long-run income in Sweden - Anders Björklund; Markus Jäntti; John E. Roemer (Institute for the Study of Labor (IZA), 2011)
Equality of opportunity is an ethical goal with almost universal appeal. The interpretation taken here is that a society has achieved equality of opportunity if it is the case that what individuals accomplish, with respect to some desirable objective, is determined wholly by their choices and personal effort, rather than by circumstances beyond their control. We use data for Swedish men born between 1955 and 1967 for whom we measure the distribution of long-run income, as well as several important background circumstances, such as parental education and income, family structure and own IQ before adulthood. We address the question: in Sweden, given its present constellation of social policies and institutions, to what extent is existing income inequality due to circumstances, as opposed to 'effort'? Our results suggest that several circumstances, importantly both parental income and own IQ, are important for long-run income inequality, but that variations in individual effort account for the most part of that inequality.
urn:nbn:de:101:1-201104113395
Keywords: D31; D63; J62; C14; 330; equality of opportunity; family background; inequality; long-run income; Soziale Gerechtigkeit; Familiensoziologie; Einkommensverteilung; Schweden